Kandungan Zat Besi (Fe) dan Daya Terima Keripik Daun Bangun-Bangun - RISANTI FEBRINE ROPITA; Prof. Dr. Ir Albiner Siagian M.Si; Dr. Ir. Zulhaida Lubis M.Kes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Abstract Bangun-bangun leaves is one of the lactagogue plants that grow in the area Batak , North Sumatra, which has been scientifically proven to increase milk production . Bangun-bangun leaves also has ferrum and high karatenoid . Consumption of these plants can increase level of ferrum , potassium , zinc , and magnesium in breast milk and infant weight gain . Chips is one kind of snack most favored by the people of Indonesia. Chips is a snack that has lasting power is quite high , good taste , and many variations so as to meet consumer tastes . Breastfeeding mothers need adequate ferrum intake for mothers during childbirth bled a lot and 50 % fetal ferrum needs from the mother . This research was conducted to see the ferrum and receive power of bangun- bangun leaves chips by breastfeeding mothers in Doloksanggul. The chips are made in the three treatments, namely sheet chips (A1), roll (A2), and sticks (A3). Organoleptic assesment of bangun-bangun leaves chips visits based on colour, flavour and texture. To determine whether there is a difference in each treatment we used analysis of variance and duncan test. To see the ferrum content in bangun-bangun leaves chips used AAS Method (Atomic Absorption Spectrophometry). The results showed that there are differences in the colour, flavour and texture of each treatment. The most preferred colour is stick chips. Most preferred flavor is stick chips. Level of texture liking for chips and crisps shaped sheet-shaped sticks are the same, whereas the level of preference chips shaped roll with chips shaped sheet and stick is different. There are differences in ferrum levels on each - each treatment bangun-bangun leaves chips. Ferrum is highest in the chips shaped rolls. Breastfeeding mothers can make bangun-bangun leaves chips as an alternative in eating the bangun-bangun leaves. In addition be made to disseminate the manufacture bangun-bangun leaves and benefits as well as more research on the diversification of food with basic ingredients bangu-bangun leaves. Keywords: Bangun-Bangun Leaves, Chips, Ferrum, Breastfeeding Mothers